Decreased BDNF in female but not male rats after exposure to stress: a sex-sensitive rat model of stress?. (3rd September 2019) - Weisbrod, Aaron S.; Barry, Erin S.; Graham, Alice M.; Eklund, Michael; Grunberg, Neil E.
Abstract: The literature has consistently emphasized a relationship between chronic stress and depression as well as the involvement of brain-derived neurotrophic factor (BDNF). It is also well known that there are gender disparities with regard to depression. However, there has been a lack of biobehavioral experimental investigations of these relationships with regard to the role of BDNF in sex differences in response to stress. It was hypothesized that stress (chronic unpredictable mild stress [CUMS], shock stress [SS]) would result in greater deleterious alterations in behavior (open field activity [OFA]) and biological (serum BDNF, body weight [BW]) indices of depression for female rats as compared to male rats. Subjects consisted of 79 Sprague-Dawley rats with 11–16 rats per each condition. CUMS consisted of 14 d of stress whereby on each stress day, rats were exposed to 20-min periods of predator stress and unpredictable environmental stress. SS consisted of a 2-h per day session of immobilization and tail-shocks repeated for three consecutive days. Serum BDNF was collected via trunk blood and quantitated using commercial enzyme-linked immunosorbent assay (ELISA). There were pronounced sex differences with regard to stress-induced behavioral and biological alterations. Both stressors decreased vertical activity (VA) (i.e. increased depressive-related behavior) and SS decreased serum BDNF in female rats, but not in male rats. Findings indicate a potential relationship between depressive-like behaviors and BDNF after exposure to stress. The clear sex differences in stress responding emphasize the need for more stress research that involves male and female subjects. Lay summary: Stress decreased vertical activity (VA) in female but not male rats while shock stress (SS) decreased serum BDNF in female but not male rats. VA was positively correlated with serum BDNF for female rats. These findings suggest sex differences in response to stress.